PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN MARITAL RAPE - Rizky Sandra Tomi; Sri Zanariyah; Mirwansyah Mirwansyah (VIVA THEMIS, 2022)
Law enforcement officials have made efforts to protect child victims of violence, including child victims of Marittal Rape (sexual violence in the family). This is because there are many child victims of marital rape in Indonesian society as has been widely reported in the mass media about acts of sexual violence committed against children by family members, whether committed by biological fathers, brothers, sisters, uncles, grandfathers and other family members. The problem studied is how is the implementation of legal protection for children as victims of marital rape? and the inhibiting factors for protecting children as victims of marital rape?The research method consists of, this type of research is normative empirical. The problem approach in this study uses a normative juridical approach and an empirical juridical approach. The type of data consists of two groups, namely primary data and secondary data. Data collection is done by literature study, field study. Data processing was carried out including data selection and data classification. The data analysis used was qualitative analysis.Legal protection for victims of criminal acts of obscenity is in accordance with Law Number 35 of 2014 concerning Child Protection Article 64 Paragraph (3) which includes rehabilitation efforts, rehabilitation efforts, both within institutions and outside institutions, efforts to protect from publicity identity through the mass media and to avoid labeling, providing safety guarantees for witnesses victims and expert witnesses, both physically, mentally and socially and providing accessibility to obtain information regarding case developments. Obstacles and solutions in implementing legal protection for child victims of abuse include: Victims of rape are individuals who suffer physically, mentally and socially due to criminal acts, even victims can suffer from prolonged fear, this is because victims of abuse besides suffering physically, also experienced great mental pressure as a result of these actions. The solution to these obstacles was that the victim was a criminal act of obscenity.